COMPARATIVE ANALYSIS OF EXTRAPOLATION METHODS OF LABORATORY DATA TO THE ECOSYSTEM LEVEL IN AQUATIC ECOTOXICOLOGY - Безвербна, Олена Вікторівна (Science-based technologies, 2019)
In order to assess the environmental effects during risk assessment, in practice it is impossible to conduct laboratory and field studies for all types of organisms in the biocenosis, as well as accurately reproduce in a laboratory experiment all combinations of conditions and factors of influence. That is why it is necessary to find the most precise model of data extrapolation from laboratory toxicological experiments - bioassays - to the level of aquatic ecosystem. Regardless of the calculation method, all such models are based on determining the predicted no-effect concentration of the pollutant for living organisms that populate the reservoir. Different methods of extrapolation of laboratory toxicity data to ecosystem level are compared by the example of determining the toxicity of phenol to water bodies. Calculation is based on bioassay results and carried out by methods of safety factors and empirical statistical models (Kooijman's method and method of Van Straalen and Denneman). The method of safety factor is the simplest and fastest, but its outcome strongly depends on the quantity and quality of the toxicity profile data and does not include the probability estimation. The safe concentration value, calculated by the method of Van Straalen and Denneman, is the highest. The error occurring during estimation of NOEC on the basis of LС(EС)50 values affects on the calculation in this case. Instead, the Kooijjman method is very precise. The safe concentration calculated according to this method is significantly understated in comparison with the results of other methods, because it strongly depends on the number of species inhabiting the aquatic ecosystem and the number of investigated test objects. It has been found that when using the Kooijman's method too high backward LС(EС)50 values of the least sensitive test objects significantly reduce the safe concentration of a pollutant. These may cause difficulties in decision-making process. In order to obtain the most reliable results, it is recommended not to consider too backward LС(EС)50 values using Kooijman's method for calculation of safe concentration of the pollutant and to take into consideration all values from LС(EС)50 calculation line using the method of Van Straalen and Denneman.